EVALUATION OF THE LIPID-LOWERING EFFECTS OF HA MO NK CAPSULES COMBINED WITH INTRAVASCULAR LASER THERAPY (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effects of  Ha mo NK capsules combined with intravascular laser therapy on serum lipid parameters in patients with dyslipidemia.Methods: A controlled, open-label clinical trial with a pre–post intervention design was conducted on 60 patients diagnosed with dyslipidemia. Participants were allocated into two groups: Group 1: Ha mo NK capsules, 6 capsules per day divided into two doses (morning and afternoon) + Atorvastatin 10 mg, 1 tablet taken at 20:00 + intravascular laser therapy, 30 minutes per session, once daily. Group 2: Atorvastatin 10 mg, 1 tablet taken at 20:00 daily for 30 days.Results: The intervention significantly reduced total cholesterol (TC) from 5.97 ± 1.68 to 4.65 ± 1.32 mmol/L, triglycerides (TG) from 4.62 ± 3.13 to 2.95 ± 2.10 mmol/L, LDL-C from 4.15 ± 1.05 to 2.98 ± 0.88 mmol/L, and non-HDL-C from 5.03 ± 1.56 to 4.10 ± 1.32 mmol/L (p < 0.05). These reductions were greater than those observed in the control group, where TC decreased from 5.88 ± 1.60 to 5.25 ± 1.21 mmol/L, TG from 4.70 ± 3.36 to 3.85 ± 2.75 mmol/L, LDL-C from 4.08 ± 1.02 to 3.55 ± 0.95 mmol/L, and non-HDL-C from 5.07 ± 1.28 to 5.01 ± 1.45 mmol/L (p < 0.05).Conclusion: Ha mo NK capsules combined with intravascular laser therapy significantly improve lipid profiles in patients with dyslipidemia.
Keywords: Dyslipidemia; Ha mo NK capsules; Intravascular laser therapy.